Fact sheets as one of the internal written communications a survey among employees of the Marco Polo Hotel of Davao - Boluso, Abigail C.
This study aimed to determine the role of the fact sheets as one of the internal written communication of the Marco Polo Hotel of Davao. These fact sheets are one of the employees' evident means of knowing what is going on in their organization. A survey was conducted among thirty employees who answered the survey questionnaires. The frequency and the percentage of the responses in a particular item of the survey questionnaire were computed. Results of this study found that The Marco Polo Hotel of Davao ensures good internal communication. Some factors, however, may just affect the employees' perception towards their fact sheets. Identifying noise as an element of the Shannon and Weaver model, reasons like manner of presentation of their fact sheets and their busy schedules leads to the employees' failure to read these fact sheets. But nonetheless, the employees have a positive response with this written communication as a source of information.